The Types of Questions Used by the Teacher in Reading Class at MTs As'adiyah Ereng-Ereng Bantaeng - Lidya Arlini; Haryanto Atmowardoyo; Kisman Salija (Madrasah Tsanawiyah DDI Cilellang, 2020)
This research highlights the types of questions used by the teacher in Reading Class which focused on teacher's question, types of the question and the length of students' responses. The research was conducted at MTs As'adiyah Ereng-Ereng Bantaeng, the researcher chose one English teacher purposively. This research applied qualitative descriptive and discourse analysis as a research design to analyze language, writing, speech, and conversation (verbal and non-verbal). The data was collected through classroom observation and interview. One teacher was involved as a subject of this research. The data were analyzed based on three procedures of data analysis which were involved in data collection, data analysis and interpretation. The result of this research shows that (1) the teacher performed both types of question from Lidya's Genre of question they are less sophisticated and sophisticated questions. In this research less sophisticated question emerged 328 times in three meetings observation. This level of question become most used level of question because basically the teacher asked question to recall the material that they have been learned before in order to involve the students' participation and to recall their memory in their teacher and learning process especially memory that related to the words meaning. In contrast, sophisticated question only appeared 106 times. The sophisticated questions demand the students to use their imagination, developed unique ideas, think creatively and making some judgment related to the teaching material based on the specific criterion. (2) The reason why teacher ask questions dominated by checking the students' understanding about the material. The types of questions asked were determined by pedagogical purposes the teacher wanted to achieve. (3) The question that achieves the longest response was less sophisticated questions (more-than-ten-words) based on the length of students 'responses and followed by sophisticated question (seven-to-ten-words) it means that when this type of question asked, the students' response was shorter.